Progress Report on the Activities of the Independent Evaluation Office. (Policy Papers; Policy Paper ;, 2012)
This report summarizes the activities of the Independent Evaluation Office (IEO) since the 2011 Annual Meetings. In this period, the IEO has advanced work on three ongoing evaluations: International Reserves: IMF Advice and Country Perspectives, The Role of the IMF as Trusted Advisor, and Learning from Experience at the IMF: An IEO Assessment of Self-Evaluation Systems. The IEO expects to submit these evaluations to the Executive Board over the course of the year. The IEO has begun consultations on topics for future evaluations and will present a tentative work program to the Executive Board for review in due course.